Структура і алгоритм роботи автоматизованої системи управління допуском авіадиспетчера до самостійної работи - Григорецький, Володимир Олексійович (НТУ "ХПІ", 2015)
У статті запропоновані принципи побудови автоматизованої системи управління допуском авіадиспетчерів до самостійної роботи з обслуговування повітряного руху. Запропонований контур підготовки авіадиспетчерів до самостійної роботи з використанням інформаційних моделей діяльності та етапи автоматизованої діагностики авіадиспетчерів. Розроблена функціональна схема автоматизованої системи управління допуском авіадиспетчерів до самостійної роботи з управління повітряним рухом. Обґрунтовано концепцію формалізації і автоматизації процесів прийняття рішення про допуск авіадиспетчерів до самостійної роботи з точки зору забезпечення безпеки польотів.

In the article the principles of automated control system for the admission of air traffic controllers to work independently of the air traffic service. The proposed circuit training air traffic controllers to work independently using information models and stages of automated diagnostics air traffic controllers. The functional scheme of automated control system for the admission of air traffic controllers to work independently of air traffic control. The concept of formalization and automation of decisions on the admission of air traffic controllers to work independently in terms of safety. Based on existing regulations and education - kfalifikatsiynyh characteristics of the air traffic controller is developed and defined the structure of standardized information models and current air traffic controllers-trainees taking into account the possibility of losing skills, and model errors. Established a relationship between elements of knowledge and skills of air traffic controllers and possible errors. Obtained principles, methods evaluation model is scientific methodic basis for the creation of automated control systems in the area of professional competence of operators particularly complex and dangerous systems. In scientific work the author considers various software failure in the system: monitoring of government air traffic; radio system; failure data lines; failure detection functions conflict.
Structure and algorithm of the automated control system for air traffic controllers admission to independent work
Keywords: управління повітряним рухом; тренажер; моделі діяльності; безпека польотів; air traffic controller; model activities; air traffic control simulator